Coordination polymer-forming liquid Cu(2-isopropylimidazolate). Issue 38 (21st September 2022) - Watcharatpong, Teerat; Pila, Taweesak; Maihom, Thana; Ogawa, Tomohiro; Kurihara, Takuya; Ohara, Koji; Inoue, Tadashi; Tabe, Hiroyasu; Wei, Yong-Sheng; Kongpatpanich, Kanokwan; Horike, Satoshi
Abstract : The melt state of coordination polymer crystals is composed of macromolecular-chain assemblies without coordination bond breaking. The coordination-polymer-forming liquid provides various morphologies, including spun fibers. Abstract : The structure of the melt state of one-dimensional (1D) coordination polymer crystal Cu(isopropylimidazolate) (melting temperature T m = 143 °C) was characterized by DSC, variable temperature PXRD, solid-state NMR (SSNMR), viscoelastic measurements, XAS, and DFT-AIMD calculations. These analyses suggested "coordination polymer-forming liquid" formation with preserved coordination bonds above T m . Variable chain configurations and moderate cohesive interaction in adjacent chains are the keys to the rarely observed polymer-forming liquid. The melt structure is reminiscent of the common 1D organic polymer melts such as entanglement or random coil structures.